PEMERIKSAAN TEKANAN DARAH GRATIS MENGGUNAKAN TENSI DIGITAL PESERTA RAKERDA PDM KABUPATEN TANGERANG - Istiyono, Yogi Priyo; Rohimah, Anni; Ghazali, Ahmad Sulton; Rasydy, La Ode Akbar; Pratiwi, Dina; Sulistyo, Suryo; Kuncoro, Banu; Fhatonah, Nuriyatul (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
The Muhammadiyah Regional Leadership (Pimpinan Daerah Muhammadiyah or PDM) of Tangerang Regency is committed to improving the welfare of the community in its area. One concrete effort to achieve this goal is by organizing free blood pressure checks using digital blood pressure monitors. This activity aims to provide easily accessible healthcare services to the public and raise awareness about the importance of monitoring blood pressure for maintaining good health. In its implementation, this community service initiative involves experienced medical professionals who conduct blood pressure examinations for participants of the Muhammadiyah Regional Leadership's (PDM) Tangerang Regency event. The examination results are directly communicated to the participants, and they receive information and education about blood pressure and the steps to maintain heart health. Overall, the health examination results, particularly body temperature checks, are very satisfactory, with 100% within the normal range. However, for blood pressure examinations, it was found that 25.37% of the participants had low blood pressure, 32.83% were in the normal range, and 41.84% had high blood pressure. With activities like this, it is hoped that participants can take the necessary preventive actions promptly. Furthermore, free blood pressure checks also serve to educate the community about the importance of a healthy lifestyle and regular health monitoring